Evaluasi Tata Kelola TI Bank Indonesia Provinsi Bengkulu dengan COBIT 2019 - Tambunan, Pieters Nicholas Paradongan; Legowo, Nilo (Universitas Multi Data Palembang, 2024)
IT Governance plays a crucial role in ensuring service quality in large organizations like Bank Indonesia, aligning IT strategies with overall business objectives. Using the COBIT 2019 framework, this research assesses the current and target capability levels to identify gaps and provide recommendations. Focused on Bengkulu Province as a Class C level, the study reveals an initial capability level of Level 1 (Initial) with a gap to reach Level 3 (Defined). To bridge this gap, Bank Indonesia Bengkulu Province should establish a dedicated IT risk management team, implement Service Level Agreements (SLAs), and align quality standards with customer needs. This paper offers empirical evidence of COBIT 2019's effectiveness in enhancing IT service quality and proposes a customized approach to integrate COBIT 2019 principles with Bank Indonesia's strategic objectives. By implementing these recommendations, Bank Indonesia can enhance its IT service quality, mitigate risks, and align with regulatory requirements.